2017
DOI: 10.1111/cen.13287
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to reconsider lobectomy in low‐risk paediatric thyroid cancer?

Abstract: Ultrasound and histopathology identify a substantial population that may be candidates for lobectomy, avoiding the risks and potential medical and psychosocial morbidity associated with total thyroidectomy. We propose a clinical framework to stimulate discussion of lobectomy as an option for low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The prevalence of any multifocal disease and bilateral multifocal disease in this study population was consistent with reported rates in the pediatric literature up to 65% and 30%, respectively . In this study, the rate of detection of multifocal disease on preoperative imaging was lower than what has previously been reported in the literature . This finding may be because of variability in sensitivity of ultrasonography detection between multiple institutions and highlights the challenges of accurate preoperative detection of multifocal disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of any multifocal disease and bilateral multifocal disease in this study population was consistent with reported rates in the pediatric literature up to 65% and 30%, respectively . In this study, the rate of detection of multifocal disease on preoperative imaging was lower than what has previously been reported in the literature . This finding may be because of variability in sensitivity of ultrasonography detection between multiple institutions and highlights the challenges of accurate preoperative detection of multifocal disease.…”
Section: Discussionsupporting
confidence: 89%
“…Preoperative knowledge of the presence of unilateral or bilateral multifocal disease is most relevant for decision-making in management of pediatric PTC given the rarity of multifocality in follicular thyroid carcinoma and the aggressiveness of medullary thyroid carcinoma, for which total thyroidectomy is uniformly performed. Still, the long-term overall survival benefit of total thyroidectomy in PTC remains unclear . Furthermore, these benefits must be weighed against the considerable risks of complications in total thyroidectomy, including hypoparathyroidism and recurrent laryngeal nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trends in the management of thyroid cancer call into question the need for routine total thyroidectomy in patients with low-risk PTC who have a nonsuspicious or cytologically benign contralateral nodule. The decrease in use of RAI ablation in patients with low-risk PTC enables lobectomy in a larger number of patients (20,21). Also, with better understanding of the epidemiology of thyroid cancer, we now know that many small thyroid cancers are "subclinical" and of little clinical significance, leading to the ATA recommendation not to perform fine-needle aspiration (FNA) for nodules smaller than 1 cm even with high-risk sonographic features and the option for active surveillance in patients with microscopic PTC (11,22).…”
mentioning
confidence: 99%
“…However, selection bias may account for some of the lack of survival benefits from total thyroidectomy, and in some studies, follow-up may not have been sufficient to draw this conclusion ( Nice et al 2015 ). Nevertheless, there is some recent evidence to suggest there may be criteria by which to define very-low risk patients who may be candidates for lobectomy rather than total thyroidectomy ( Kluijfhout et al 2017 ).…”
Section: Resultsmentioning
confidence: 99%